Edaravone dexborneol alleviates neuronal senescence injury by mitigating the innate immune response - Jingxian Sun; Mingsheng Yu; Haowei Li; Lin Ma (Tissue and Cell, 2027)

Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

Site-specific promoter hypermethylation of GPX4 in heart failure with reduced ejection fraction (HFrEF): nonlinear dose-response with hepatic and coagulation markers - Lin Ma; Xiangwen Li; Dandan Zhang; Li Song; Yu Guo; Leyi Wang; Rongqiang Zhang (Molecular Biology Reports, 2026)

Dysregulated methylation of the human BOLL promoter hinders germ cell development from spermatogonia to spermatids - Tsung-Yen Lin; Hsing-Yi Chen; Yung-Hsuan Cheng; Chun-Wun Lu; Hsiu-Yen Ma; Hsiu-Chiung Hou; Yung-Ming Lin; Shih-Chieh Lin; Yu-Sheng Cheng (Molecular Biology Reports, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Resource overlap drove cultural integration on the northeastern Tibetan Plateau during the mid-late Holocene: A case study of the Majiayao and Zongri cultures - Yu Du; Guangliang Hou; Xuefeng Sun; Gaojun Li; Xin Lin; Qianqian Wang; Shuguang Ma (Quaternary Science Reviews, 2026)

Late Cretaceous large-scale melting of the Neo-Tethyan oceanic slab in southern Tibet - Cheng Li; Lin Ma; Andrew C. Kerr; Qiang Wang; Zhiwei Yu; Wei Qiao (Lithos, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Injectable, adhesive, and ROS-responsive hydrogel loaded with curcumin and bFGF for enhanced oral ulcer healing - Yaru Zhang; Zengqi Ye; Chenhui Chen; Jiancheng Yu; Yihao Wu; Ziqi Yu; Yue Huang; Yangshuai Jin; Xian Tong; Li Zhu; Jixing Lin; Xiaojun Cai; et al. (Chemical Engineering Journal, 2026)

Nano-island Cu–Cu2O heterojunctions: Synergistic electroreduction of bromate at mixed-valence perimeters - Yu Chu; Junjie Li; Huihuan Lin; Binyu Ma; Zhipeng Luo; Yue Cheng; Xin Yu; Huabin Zeng (Journal of Water Process Engineering, 2026)

Ru-Co bimetallic catalysts with synergistic crystalline phase regulation and hydrogen spillover for deep hydrodeoxygenation of lignin oil - Jing-jing Wu; Jia-yuan Tian; Feng Lin; Yu-long Ma; Yong-gang Sun; Pei Ma; Shuai-lei Li; Xue Zhang; Yi-shu Ma; Xiao-lin Xue (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Coumarin constituents from Gerbera delavayi: Anti-inflammatory and anti-tumor activities with chemotaxonomic significance - Yan Zhong; Yu-Shuang Wen; Ying-Jie Xu; Chun-Hua Liu; Xue Ma; Yong-Lin Wang; Yong-Jun Li; Li Jiang (Biochemical Systematics and Ecology, 2026)

Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

New multisource data-driven gap-filling approaches for meteorological data measured at eddy flux sites - Tao Li; Zhi Chen; Yong Lin; Lexin Ma; Fubo Yu; Hyun Seok Kim; Kazuhito Ichii; Yoshiyuki Takahashi; Guirui Yu (Agricultural and Forest Meteorology, 2026)

Water-MAS: A multi-agent LLM framework with instruction-data decoupling for smart water management - Fangkun Lin; Zhipeng Luo; Binyu Ma; Zhiyu Zhang; Kaiyan Liu; Xin Yu; Boyan Xu; Huabin Zeng (Water Research, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Strong metal-support interaction boosts the activity and stability of CeO2 supported Pt nanocatalysts for dichloromethane oxidation - Xiuguan Liu; Maosen Xu; Qi Lin; Pengcheng Yu; Yuanhao Ye; Hongli Liu; Deyun Ma (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Scenario-based mapping reveals soil organic carbon responses to land-use change in the Amazon Basin - Lanji Ma; Jiaxue Wang; Yujiao Wei; Peiheng Yu; Yongsheng Hong; Zihao Wu; Yaolin Liu; Gan-Lin Zhang; José A.M. Demattê; Budiman Minasny; Yiyun Chen (CATENA, 2026)

Stakeholder priorities dominate the evaluation of climate change impacts on ecosystem-service multifunctionality - Xin Jing; Hao Wang; Wei Xu; Xiaomin Fan; Lin Jiang; Yu Li; Zhiyuan Ma; Peter Manning; Nathan J. Sanders; Bernhard Schmid; Yunfeng Yang; Zhenhua Zhang; et al. (Science China Life Sciences, 2026)

A domain-enhanced multi-agent framework for trustworthy literature screening in water research - Runzhi Wang; Xinlu Lin; Baoyi Zhong; Jiaxuan Li; Ruixing Huang; Yu Huang; Yajuan Cai; Chotiwat Jantarakasem; Yang Xiang; Konstantinos Plakas; Jun Ma; Yumeng Zhao (Water Research, 2026)

Prediction of energy consumption and carbon emission in Yunnan Province based on LEAP modeling - Zhengyuan Fan; Jie Yu; Taiwei Gu; Cui Qiao; Shaoyuan Li; Lin Ma; Wenhui Ma (Utilities Policy, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Impacts of steam explosion treatment on qualities, protein network development and digestion-resistant properties of dried sorghum noodles - Kun Yu; Xiaoli Ma; Jingjie Lin; Yuan Zhang; Chunxu Chen; Di Wu; Peiyan Li; Guoyuan Xiong (Food Chemistry, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Longitudinal trends in serum triclocarban levels from 2008 to 2018: Evidence from the prospective Dongfeng–Tongji cohort study - Caizheng Yu; Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Meian He (Environmental Research, 2026)

Coupled water-heat-salt transport in the vadose zone of loess: A numerical framework considering phase changes and ionic fractionation - Shi-Feng Lu; Jia-Qi Yu; Meng-Yuan Ma; Xiao-Lin Huang; Ling Xu (Computers and Geotechnics, 2026)

Highly uniform Cu/Fe-LDH synthesized by a UNISON method for MRI-guided ferroptosis/cuproptosis therapy and immune microenvironment remodeling of tumors - Chunmei Chen; Bin Ren; Qingdeng Fan; Ya Huang; Xinyu Chen; Yurun Huang; Hang Yi; Guochao Wu; Jing Yang; Lin Huang; Jiaoyang Zhu; Haolong Ma; et al. (Chemical Engineering Journal, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Shared inflammatory targets of phthalate plasticizers in MODS-related syndromes: An integrative network toxicology study with representative DEHP in vitro validation - Lin Song; Aifeng He; Wei Jiang; Ke Liu; Jingyi Ma; Jing Wang; Keran Shi; Jiangquan Yu; Ruiqiang Zheng (Toxicology and Applied Pharmacology, 2026)

Inhibitory effects and kinetics of Sudan dyes on human carboxylesterases - Yu-Zhi Fan; Chen-Yuan Liao; Jia-Min Gong; Yu-Xin Yang; Yu-Lin Ma; Zhen-Zhong Liu; Zuo Du (Toxicology and Applied Pharmacology, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

The 15-15 rule for healthy cities: An operational subject-object integrated model to bridge greenspace accessibility and effective exposure in environmental planning - Yuxuan Wang; Zhaowu Yu; Gaoyuan Yang; Tao Lin; Weiyuan Ma; Junhong Zhong; Mincong Wang; Huiwen Zhang (Journal of Environmental Management, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Boosting pH-universal hydrogen evolution of the In/Cu3P Mott-Schottky heterojunction electrocatalyst by constructing the ohmic contact and promoting water activation - Pengfei Du; Fang Li; Huiqin Yu; Jing Cao; Yuan Ma; Haili Lin (Fuel, 2026)

Synergistic effects of biochar application and wide-precision planting on wheat yield: Optimizing canopy structure and facilitating deep root growth - Menghan Jia; Jiayue Dai; Zeping Shi; Yehan Fu; Yu Cheng; Yixuan Lin; Baodi Dong; Lijuan Zhang; Yuzhao Ma (Field Crops Research, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

Effects of dietary Zn deficiency and excess on growth performance, glycolipid metabolism, and intestinal homeostasis of juvenile golden pompano (Trachinotus ovatus) - Hongkai Ye; Zhanzhan Wang; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Aquaculture International, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

A Modified FMEA Framework Incorporating Confidence-Enhanced Probabilistic Linguistic Modeling and Weighted Hypergraph Propagation for LNG Storage Tank Risk Assessment - Yang Yu; Jiandong Ma; Jianxing Yu; Peimin Li; Lin Song; Yuheng Yang; Zhenglong Yang (Journal of Marine Science and Engineering, 2026)
LNG storage tanks are essential facilities for large-scale storage and transportation of cryogenic energy. Because of the flammable, explosive, and ultra-low-temperature characteristics of liquefied natural gas, failures in such systems may result in serious consequences for operational safety and the surrounding environment. Effective identification and prioritization of potential failure modes are therefore crucial for safe operation. Failure mode and effects analysis (FMEA) has been widely applied in risk assessment, yet conventional FMEA methods still show limited capability in describing uncertain linguistic evaluation information, reflecting the reliability of expert judgments, and representing high-order coupling relationships among failure modes. To address these issues, this study develops a modified FMEA framework that integrates confidence-enhanced probabilistic linguistic modeling with weighted hypergraph propagation for LNG storage tank risk assessment. In the proposed framework, confidence-enhanced probabilistic linguistic term sets are employed to represent the fuzziness, probabilistic preference, and reliability differences contained in expert assessments. A confidence-adaptive scoring function is further constructed to strengthen the discrimination of risk quantification by capturing structural differences in probability distributions without introducing externally specified parameters. Meanwhile, the importance of risk factors is determined through a combined subjective–objective weighting strategy, and a weighted hypergraph propagation mechanism is established to characterize high-order structural associations among failure modes and to revise baseline risk levels through a node–hyperedge–node transmission process. A case study of a large LNG storage tank system in Tangshan, China, is carried out to examine the applicability and effectiveness of the proposed framework. The results demonstrate that the proposed method can effectively integrate complex expert evaluation information with structural coupling effects, while sensitivity and comparative analyses further confirm its robustness and suitability for failure risk prioritization in LNG storage tanks.

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Differential effects of sulfide-induced transformation of biodegradable and conventional microplastics on sedimentary CO2 and CH4 emissions: Underlying microbiome-mediated mechanisms - Jinying Hu; Wenjuan He; Zhexi Liu; Qi Qiao; Lizi Zhao; Yuanyuan Li; Mengyu Ma; Hanbo Yu; Lin Shi; Jinhui Huang (Environmental Research, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

N-heterocycle substitution engineering on tetra-coordinated boron framework for high-performance narrow-band bidentate Pt(II) complex phosphor - Zhao Feng; Siqi Liu; Ziyi Chen; Xiong Huang; Jie Zhang; Ruiqin Zhu; Lin Ma; Yue Yu; Daokun Zhong; Yuanhui Sun; Xiaolong Yang; Guijiang Zhou (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Prediction of clock bias for BeiDou satellites using a combination of variational mode decomposition and long short-term memory network - Wenlong Sun; Fengfeng Shi; Yuting Lin; Jinfeng Xu; Guojun Li; Guocheng Wang; Shaofeng He; Jiawei Yu; Pei Ma (Journal of Geodesy, 2026)

Key Parameters Prediction of Shale Reservoir Based on Deep-Learning Model: A Case Study of Jurassic Da’anzhai Member in Sichuan Basin - Wenqiang Tang; Chao Ma; Shengjian Zhou; Shaomin Zhang; Qiyu Wang; Kunyu Wu; Haitao Hong; Jiashan Lin; Yun Yang; Kai Yu (Journal of Earth Science, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

Quantifying evapotranspiration and shading cooling of urban vegetation across climates under extreme heat using an integrated SCOPE-SEB model and surface temperature analysis - Zhaowu Yu; Mingchuan Shao; Wenjun Yang; Yujia Zhang; Yuxia Hu; Wenjuan Ma; Junhong Zhong; Yanghan Lin; Mincong Wang; Huiwen Zhang; Jiquan Chen; Chenghao Wang; et al. (Remote Sensing of Environment, 2026)

Anomaly detection for LNG storage tanks with limited sensor data using WGAN-CADA and multi-branch probabilistic autoencoder - Yang Yu; Jiandong Ma; Jianxing Yu; Zihang Jin; Hanxu Tian; Yuheng Yang; Lin Song (Process Safety and Environmental Protection, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Tailoring properties of corn starch via active extrusion: Key role of feed moisture - Xiaoshuai Yu; Jiangkai Zeng; Jinjie Huo; Jinming Ma; Jiaqi Song; Lin Wang; Mohamed E. Hassan; Yixin Peng; Bo Bo; Zhigang Xiao; Yumin Duan (Journal of Food Engineering, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Divergent response of vegetation structure to land-atmosphere droughts across aridity gradients in the Northern Hemisphere - Bingxin Ma; Longhui Li; Yue Zhang; Yueyue Dou; Lin Yu (Global and Planetary Change, 2026)

Hierarchical intelligent braided silk yarns for ligament reconstruction and prognosis assessment - Ke Ma; Ke Wang; Shou-Shan Yu; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Decomposition characteristics of woody peat and its mixtures with liable organic materials in a newly reclaimed saline-alkali soil: A one-year incubation experiment - Yanyun ZHENG; Zhenghong YU; Jiabao ZHANG; Congzhi ZHANG; Donghao MA; Lin CHEN; Guixiang ZHOU (Pedosphere, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Raman-based profiling of microplastics in human uterine tissue: A new dimension in reproductive toxicology - Jingjing Peng; Yaying Lin; Fangfang Yao; Ding Ma; Jinjin Yu; Chunlin Dong (Journal of Environmental Chemical Engineering, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Bioinspired capillary-transport membranes with bubble-guided and gel channels for efficient dye salt separation at ultra-low-pressure - Wensong Ma; Ligang Lin; Hongchao Li; Zining Guo; Jing Yang; Mengfan Hou; Qi Wang; Bingchen Yu; Zhize Yu; Xu Yang (Chemical Engineering Journal, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Controls of organic matter sources and hydrodynamic conditions on carbon and phosphorus contents in two karst reservoirs - Wenhui Wang; Yan Zeng; Jia Yu; Zhenzhen Ma; Yaoting Lu; Zuxue Jin; Lin Shi; Shuyun Xie; Jingfu Wang; Jingan Chen (Applied Geochemistry, 2026)

DKK1 expression associates with tertiary lymphoid structure maturity in non-small cell lung cancer - Lin Ma; Linlin Yang; Junxu Wen; Fei Lu; Jinming Yu; Xiangjiao Meng (Apoptosis, 2026)

Experimental Study on Hydrodynamic Responses of Multi-Body Floating Systems Under Combined Wind, Wave, and Current Loads - Lin Song; Jianxing Yu; Hanxu Tian; Ruilong Gao; Jiandong Ma; Zihang Jin (Journal of Marine Science and Engineering, 2026)
As the development of the ocean extends to the deep and open seas, the application of multi-hull floating systems is becoming increasingly widespread, covering offshore oil and gas transfer and material replenishment operations. In multi-body floating systems, the hydrodynamic interactions between adjacent floating bodies significantly affect the overall motion response and load distribution. However, there is currently a lack of systematic experimental research on systems involving three or more units under the combined action of wind, waves, and currents. This study presents a 1:50 scale model experiment on a five-body offshore replenishment station, comprising a central transfer platform and four surrounding vessels. Absolute six-degree-of-freedom motions and relative displacements between the transfer platform and neighboring vessels were measured. The results indicate distinct differences among the units. The peripheral vessels have greater horizontal and yaw motions, while the central units are more restricted. The relative motions are substantially increased for beam and oblique wave conditions, implying increased interaction effects in the gaps between neighboring bodies. Moreover, the combined oblique environmental loading and asymmetric mooring stiffness result in increased global drift and yaw motions. These findings provide benchmark data for numerical validation and practical guidance for the design and operation of multi-body floating systems.

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Exposure trends of neonicotinoids from 2008 to 2018 and health risk in a longitudinal study in China - Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Caizheng Yu; Meian He (Environmental Research, 2026)

Utilizing conjugation effect of nitrogen unshared electron to architect redox-active polymer for sodium-ion storage - Liang-Yu Wang; Shun-Yu Yao; Jing-Zhe Wan; Qi-Hang Wang; Chao Ma; Jiu-Lin Wang; Kai-Xue Wang (Chemical Engineering Journal, 2026)

Spatiotemporal characteristics of the vehicle-cabin thermal environment and occupant thermal responses under strong summer solar radiation - Yuxin Yang; Rui Zhao; Juan Yu; Deyin Zhang; Borong Lin; Kaiyue Ma; Xi Zhang; Haifeng Xia (Building and Environment, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Structural design of wheat gluten using twin-screw extrusion: Focus on its application in starch-based gels - Xiaoshuai Yu; Zongrui Liu; Xiaoting Ma; Jiangkai Zeng; Jinjie Huo; Yumin Duan; Xiaoqi Ma; Lin Wang; Yixin Peng; Peng Wang; Zhigang Xiao (Journal of Cereal Science, 2026)

Impact of rice protein amyloid fibrils on texture, flavor, digestibility and structural properties of extruded soy protein isolate - Jinming Ma; Deyin Pan; Peng Wang; Xiaoqi Ma; Lin Wang; Mohamed E. Hassan; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Construction of 3D printable native-modified corn starch composites gels as dysphagia diet: Crucial role of modified starch - Jiangkai Zeng; Yumin Duan; Zaifei Zheng; Peng Wang; Xiaoqi Ma; Lin Wang; Chong Cui; Bo Bo; Xiaoshuai Yu; Zhigang Xiao (Food Research International, 2026)

Molecular and functional characterization of interleukin-1β in red drum (Sciaenops ocellatus) and its pivotal role in antibacterial immunity - Lin Zhang; Jinglu Ma; Jingyao Yu; Qing Chu (Fish & Shellfish Immunology, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

A new fucosylated glucuronoxylomannan from the fruit bodies of Tremella aurantia: structural characterization and immunoenhancing activity on seasonal influenza mRNA vaccine - Jing Chen; Yuan Ma; Zhi-Min Rao; Song-Lin Jiang; Ying-Jun Lou; Karim Malik; Arman Chowdhury; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

piR-16404 drives ferroptotic liver injury via CASTOR1/mTORC1/GPX4 dysregulation in HepG2 cells and mice: a novel toxicity mechanism of N, N-dimethylformamide - Wanli Ma; Xiaoyu Huo; Ruoxi Li; Jingjing Xing; Lin Xu; Dianke Yu (Archives of Toxicology, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Organophosphate esters (OPEs) in a marine food web of the Yellow Sea, China: Bioaccumulation, trophodynamics, and model prediction - Baolin Liu; Xinyu Ma; Xiaosheng Lin; Junjie Li; Sixu Liu; Weihua Dong; Yong Yu (Marine Pollution Bulletin, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

An automated and intelligent monitoring system for shield tunneling muck evaluation integrating multimodal data - Zeyu Yue; Linchong Huang; Yuexiang Lin; Yu Liang; Mingfeng Lei; Jianjun Ma (Journal of Cleaner Production, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Performance evaluation and solidification mechanism of soybean urease combined with gypsum-urea for improving saline soil - Hang Shu; Siqi Li; Qiang Ma; Qingbo Yu; Lei Xi; Weiqing Lin; Yongli Liu (Journal of Environmental Management, 2026)

Dual influences of the allergenicity of Atlantic cod parvalbumin fermented by Lactobacillus helveticus - Shuai Ma; Xitong Yu; Hao Wang; Liwei Wang; Tingyu Zhang; Yumiao Bian; Mengxin Wang; Zhenxing Li; Ziye Zhang; Hong Lin (Food Bioscience, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

Terminal-carboxyl-engineered 3D PLA nanochannels via ionic liquid templating for high osmotic energy conversion - Leqi Chang; Cuncai Lin; Xingteng Ma; Yuankun Ning; Zeyang Yu; Shuhong Hu; Yanshu Chen; Xin Sui; Longcheng Gao; Kunyan Sui (Chemical Engineering Journal, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

The spatio-temporal evolution of ecosystem service value and its driving factors analysis in Shandong Province of China - Dongling Ma; Zhenxin Lin; Qian Wang; Yifan Yu; Guoqiang Yu (Advances in Space Research, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Surrogate-based global sensitivity analysis of a floating fish cage array with shared mooring - Yu Ma; Zhiyu Jiang; Muk Chen Ong; Lin Li (Ocean Engineering, 2025)

Temperature-dependent expression profiling of 16 HSP genes across developmental stages in Frankliniella occidentalis - Lin Shu; Yi-Jie Ma; Yu-Cheng Wang; Ya-Wen Chang; Yu-Zhou Du (Journal of Thermal Biology, 2025)

Intercity red meat trade exacerbates the spatial inequality of greenhouse gas emissions and health burdens in China - Yue Zhao; Le Yu; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2025)

Combined stressors of copper and antibiotics alter nitrogen transformation and multifunctionality of constructed wetlands: Responses of microbes and macrophytes - Lin Ma; Desheng Yu; Xiaokan Wang; Guihua Liu; Wenzhi Liu; Gang He (Journal of Environmental Management, 2025)

Optimizing the biosynthesis factors and screening the metal chelation capacity of Yersinabactin analogs from genetic engineering bacteria: The promising agents for environment protection - Haotian Liu; Huiping Ma; Ziqi Ren; Zhaoshuo Liu; Jianli Liu; Jiahe Chen; Jianxiang Ma; Yu Qiang; Zixuan Lin; Ruiquan Qi (Journal of Environmental Chemical Engineering, 2025)

Trade of crop products contribute to the alleviation of global nitrate leaching risks - Xuchong Chen; Ling Liu; Yu Lu; Xuan Wang; Zhaohai Bai; Lin Ma (Global Environmental Change, 2025)

Long-term effects of the hydrophilic and electrophilic modified magnetic carriers on partial nitrification at low temperatures: Enhancing nitrite supply by stimulating major enzyme gene expression - Fang Man; Yi Xue; Yuexin Yu; Chengyu Gu; Sijia Ma; Yuan Lin; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Recent advances of multivalent metal nanozymes in analysis and detection - Zhao Li; Weidan Na; Chuangeng Tian; Jianguo Dong; Lin Tian; Ming Ma; Tognxiang Li; Yu Zhang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Dynamic snake vision mask r-cnn: a method for microfracture detection in electrical logging imaging - Yihang Lu; Sinan Fang; Yi Yu; Huimin Wu; Guilan Lin; Guohao Ma; Zehan Wang (Earth Science Informatics, 2025)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

High-resolution assessment reveals underestimated human health risks of ammonia emissions in China's pig production - Yue Zhao; Le Yu; Zhenrong Du; Zhaohai Bai; Ling Liu; Tao Liu; Lin Ma (Journal of Cleaner Production, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Microplastic accumulation in endometrial cancer tissues and its metabolic impact - Chunlin Dong; Hongwen Xu; Bing Zhang; Yaying Lin; Jing Song; Jinjin Yu; Ding Ma (Environmental Pollution, 2025)

Integrated analysis of lncRNA-miRNA-mRNA regulatory network revealing molecular mechanisms of immune response and ion transport in Eriocheir sinensis under alkalinity stress - Jun-Lei Ma; Yu-Lin Bai; Yi-Dong Liang; Ting Zhang; Lei You; Dong-Po Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

Targeting cuproptosis by FDX1 in acetaminophen-induced liver injury - Yan Liu; Ying Yang; Baizhao Peng; Zhongyue Ou; Anna Zuo; Zihao Jiang; Chuanghai Wu; Hiu Yee Kwan; Ke Ma; Lin Yu; Xiaoshan Zhao (Chemico-Biological Interactions, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Product and mechanistic insights into the ozonolysis of Δ3-Carene - Xulian Song; Xiaoxiao Lin; Yu Xia; Ziji Ma; Liqin Jin; Weijun Zhang; Zhandong Wang; Christa Fittschen; Xiaofeng Tang (Atmospheric Environment, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Binding of Chinese quince oligomeric proanthocyanidins with different structures to sarcoplasmic and myofibrillar protein in chicken: Role of conformational changes and heterocyclic amine inhibition - Mei-Qi Yang; Hao Liu; Yi-Lin Chen; Jia-Hao Wang; Lin Xiao; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma (Food Chemistry, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Mechanical robust and recyclable PLA-based polyurethane elastomers for flexible electronics - Chen-Yu Wang; Ke Ma; Xiao-Xue Wang; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2025)

Synergistic solar-magnetic desalination via covalently anchored Fe₃O₄/hydrogel composites - Juan Du; Hao Fang; Jialiang Ma; Jing Lin; Shikuo Li; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2025)

C2-symmetric chiral Pd(0) complexes bearing C2-symmetric chiral bidentate phosphine ligands with high luminescence dissymmetry factors and strong electroluminescence ability - Zhao Feng; Ruiqin Zhu; Lin Ma; Yue Yu; Daokun Zhong; Ziyi Chen; Tao Shi; Bochao Su; Xiaolong Yang; Yuanhui Sun; Guijiang Zhou (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Mechanical behavior of shale considering spatial variability of matrix properties - Yu Lin; Chuan He; Guowen Xu; Haojie Liu; Xu Chen; Gaoyu Ma (Bulletin of Engineering Geology and the Environment, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Evaluation of the inhibitory effects of carbamate pesticides on human carboxylesterases - Chen-yuan Liao; Xiao-lei Yi; Yu-xin Yang; Jia-min Gong; Yu-Lin Ma; Fei Long; Zhen-zhong Liu; Zuo Du (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Algae biofilm produces less microbe-derived dissolved organic nitrogen under higher C/N ratio conditions - Yuexin Yu; Yuan Lin; Chengyu Gu; Fang Man; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

“Zombie” cell drug delivery system: A novel strategy for the treatment of cancer and inflammation-related diseases - Zhouru Wang; Wenjing Yang; Danhua Liu; Peihong Lin; Rui Gao; Zhen Ma; Qiao Wang; Zhan Tang; Jie Fang; Wenying Yu (Chemical Engineering Journal, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

Rationally designed and facilely constructed CoFe2O4@SiO2 yolk@shell heterostructure spherical jars as interlayer achieve high-performance Li S batteries via “3 + 1” modal anchoring & catalyzing coupled with microreactor - Yingying Bao; Bin Yue; Lin Li; Shan Jiang; Hong Shao; Yunrui Xie; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

Quantifying mutual transport contributions of ozone and its precursors among adjacent county-level cities during typical pollution episodes - Demian Lai; Yifei Chen; Yangjun Wang; Yan Zhang; Lin Xu; Zijia Ma; Burcak Kaynak; Shikang Tao; Yu Shang; Li Li (Urban Climate, 2025)

CRISPR/Cas9 mediated knockout of laccase2 impairs cuticle tanning and pigmentation in the tobacco cutworm, Spodoptera litura - Yingchuan Peng; Yu He; Xinyi Ling; Lin Zeng; Lixia Cao; Lexin Xie; Long Ma; Wanna Zhang; Zhongqiang Jia (Pesticide Biochemistry and Physiology, 2025)

Distribution of and associations between ARGs and pathogenic bacteria in soils affected by heavy metal contamination in mining areas - Yanbin Du; Yijia Liu; Caihong Yu; Xuesong Hu; Suya Ma; Jiacheng Zou; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang (Journal of Environmental Chemical Engineering, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Using machine learning algorithm to predict lighting energy consumption of daylight-linked lighting systems from spatial daylight autonomy - Yu Bian; Yuan Zhou; Shiying Yang; Dandan Lin; Yuan Ma (Energy and Buildings, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Path tracking control of paddy field weeder integrated with satellite and visual methods - Dongshun Chen; Qiaolong Wang; Yi Lin; Zenghong Ma; Liang Sun; Gaohong Yu (Computers and Electronics in Agriculture, 2025)

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Hypertums A−J, bioactive polycyclic polyprenylated acylphloroglucinols with diverse skeletons from Hypericum perforatum L. (St. John's wort) - Wu-Yang Liu; Lin-Lin Gao; Wei Zhou; Yu-Na Ma; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2025)

Tetraphenylethene-based covalent organic polymers with tunable Electrochemiluminescence for ultrasensitive detection of tetracycline - Ziqi Lian; Zhoumei Lin; Yu Wang; Li Tan; Wenjing Gao; Yuchan Liu; Huizhen Ma; Junqiang Luo; Chenyao Chen; Wanzhen Chen; Rongkai Ye; Ying Ma; et al. (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Construction of PtFe/FeOx-Al2O3 interface via regulating the metal – support interactions for selective hydrogenation of cinnamaldehyde - Zequan Ma; Yilin Dong; Xu Tan; Jia Xue; Xiaoge Li; Yu Gu; Hui Shi; Lin-Wei Chen; Kun Wang; Lei Wang (Chemical Engineering Journal, 2025)

Fabrication of self-supporting hierarchical porous metallic glass for pH-universal hydrogen evolution reaction - Xingran Zhao; Junsheng Liu; Heting Zhang; Jihan Jiang; Jiaqing Lin; Jianan Fu; Yu Zhang; Xin Li; Wenqing Ruan; Jiang Ma (Chemical Engineering Journal, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Rodent Bioturbation Significantly Enhances Annual Methane Uptake by Tibetan Alpine Grasslands - Dezhao Gan; Dongsheng Yu; Hongchao Zuo; Zheng Li; Zelong Zhang; Huinan Li; Zhenrong Lin; Hui Wang; Qingping Zhou; Jinsong Wang; Shuli Niu; Ruijun Long; et al. (Global Change Biology, 2025)
Tibetan alpine grasslands (AG) serve as critical methane (CH 4 ) sinks, yet face degradation from anthropogenic and climatic disturbances that promote subterranean rodents (e.g., Plateau zokor [ Myospalax baileyi ] and pika [ Ochotona curzoniae ]) activities. Although rodent bioturbation (e.g., burrowing, foraging and excreting) alters soil structure, soil physico‐chemical properties and productivity from AG, its impacts on CH 4 uptake remain poorly understood. Among the first, we combined paired year‐round CH 4 flux measurements from Plateau zokor mounds (ZM) and surrounding healthy meadow (HM) patches in Tibetan alpine meadow with collated CH 4 fluxes from meta‐ and synthetic analyses across Tibetan AG, temperate grasslands (TG) and tropical grasslands (TrG) globally. We observed that rodent bioturbation significantly ( p 4 uptake (HM: −0.91 ± 0.08 kg C ha −1 vs. ZM: −1.80 ± 0.19 kg C ha −1 , mean ± standard error, negative values indicate uptake). Notably, 67% of this net increase (−0.89 ± 0.10 kg C ha −1 year −1 ) due to rodent bioturbation occurred during the growing season. Meta‐analysis results revealed this phenomenon associated with significantly ( p pmoA for methanotrophs. Non‐growing season (NGS) CH 4 uptake contributed 45% and 39% to annual CH 4 uptake for HM and ZM, respectively, falling into the ranges of 12%–64% NGS CH 4 uptake contributions from TG to AG of China. The TrG showed significant ( p 4 uptake than TG and AG globally, due to the fact that significant ( p 4 flux changes and highlight soil moisture as a key driver for global CH 4 sink variations. These results emphasise the need for long‐term monitoring to better assess the ecological consequences of bioturbation in climate‐sensitive alpine ecosystems.

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Polyhalogenated heterocycle additive induced in-situ 3D gelatinous polymerization with polysulfides for shuttle effect inhibited lithium-sulfur batteries - Xingkai Ma; Xinmei Song; Yaoda Wang; Junchuan Liang; Tianyu Shen; Zuoao Wu; Lina Qin; Huan Li; Tianchen Yu; Huaizhu Wang; Zuoxiu Tie; Yichao Yan; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Real and long-time predicting the trajectories of internal solitary waves: Case studies in the Sulu Sea - Longyu Huang; Jingsong Yang; Lin Ren; Zetai Ma; Yu Chai; Peng Chen; Shuangyan He; Bingqing Liu; Antony K. Liu (Ocean Engineering, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Deciphering the role of extracellular polymeric substances in the adsorption of perfluorooctanoic acid during sludge alkaline fermentation: Experimental study and molecular dynamics simulation - Chengyu Gu; Sijia Ma; Fang Man; Yuexin Yu; Yuan Lin; Yi Xue; Yanru Wang; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Enhancing the Fe3+/Fe2+ biocatalytic cycle using deoxidizing and iron-releasing sticks to improve bio-fenton efficiency - Chi-Wen Lin; Chung-Yen Yeh; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Source-oriented comprehensive assessment framework for identifying priority heavy metals in agricultural soils - Furong Yu; Yuekun Ji; Lin Wu; Jianuo Zhang; Yu Fu; Songtao Liu; Jianqin Ma (Journal of Environmental Chemical Engineering, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

Surgical treatment of Meniere’s disease - Yixu Wang; Hongwei Zheng; Xin Ma; Lin Han; Tongxiang Diao; Lisheng Yu; Maoli Duan (Science Bulletin, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

Metagenomic deciphers the mobility and bacterial hosts of antibiotic resistance genes under antibiotics and heavy metals co-selection pressures in constructed wetlands - Meng-Fei Yu; Luwen Chen; Guihua Liu; Wenzhi Liu; Yuyi Yang; Lin Ma (Environmental Research, 2025)

Application of nail analysis in human biomonitoring of toxic pollutants: A review - Zhuowen Li; Yanji Qu; Meiqing Lin; Yingxin Yu; Shengtao Ma (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Asymmetric environmental responses on evapotranspiration in Tibetan Plateau grassland - Lexin Ma; Zhi Chen; Guirui Yu; Tianxiang Hao; Meng Yang; Quanhong Lin; Linfei Yu (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Hydrogel-filled micropipette enables antifouling in vivo iontronic sensing - Guangguo Guo; Yifei Pan; Tianyi Xiong; Wenliang Ji; Wenjie Ma; Ping Yu; Yuqing Lin; Lanqun Mao (Science Bulletin, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

A new late-diverging non-hadrosaurid hadrosauroid (Dinosauria: Ornithopoda) from southwest China: Support for interchange of dinosaur faunas across East Asia during the Late Cretaceous - Hui Dai; Qingyu Ma; Can Xiong; Yu Lin; Hui Zeng; Chao Tan; Jun Wang; Yuguang Zhang; Hai Xing (Cretaceous Research, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Sexual dimorphism of plateau brown frog in Haibei region of Qinghai in China - Xuze Zhang; Xiaodong Ma; Fei Peng; Yi Yu; Xinrong Lin; Jinliang Wei; Yingfang Shen (Zoologischer Anzeiger, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Upcycling Nickel Ions into self-supported Electrocatalyst by using ZIF-8/Bacterial cellulose adsorbent - Jian-Yu Wu; Tian Liu; Lin Ma; Xian-Zhong Fu; Zhi-Yan Guo; Kim Meow Liew; Wen-Wei Li (Resources, Conservation and Recycling, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

EIF4A3-Induced Circ_0059914 Promoted Angiogenesis and EMT of Glioma via the miR-1249/VEGFA Pathway - Wei Yu; Duo Chen; Li Ma; Yuancai Lin; Jihui Zheng; Xinxing Li (Molecular Neurobiology, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Abnormalities of resting-state EEG microstates in older adults with cognitive frailty - Yu Zhang; Yue Ma; Yu-Lin Gao; Hai-Chao Fu (GeroScience, 2024)

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Sulforaphane acts through the NFE2L2/AMPK signaling pathway to protect boar spermatozoa from cryoinjury by activating antioxidant defenses - Guangzhi Zhang; Fei Wen; Yu Li; Pingyu Sun; Yang Li; Zhangtao Hu; Hui Wang; Yunhui Ma; Guodong Liang; Lin Chen; Ke Yang; Jianhong Hu (Theriogenology, 2024)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Differential mineral diagenetic evolution of lacustrine shale: Implications for CO2 storage - Liu Wang; Bo Liu; Longhui Bai; Lin Ma; Zhichao Yu; Qiuli Huo; Kevin G. Taylor (International Journal of Coal Geology, 2024)

Synthesis of cholesterol analogues and comparison on their effect on plasma cholesterol with β-Sitosterol - Hanyue Zhu; Longjian Chen; Zi-Xing Chen; Huiqi Lin; Jianhui Liu; Erika Kwek; Ka Ying Ma; Wensen He; Guoxin Wang; Zhen-Yu Chen (Food Chemistry, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Genome-Based Classification of ‘Haloarcula aidinensis’ and Description of Three Novel Halophilic Archaea Isolated from an Inland Saline Lake, Coastal Saline Soil, and a Marine Solar Saltern - Xue Ma; Yao Hu; Jing Hou; Yu-Guang Zhou; Heng-Lin Cui (Current Microbiology, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Tunnelling-induced nonlinear responses of continuous pipelines resting on tensionless Winkler foundation - Cungang Lin; Zhongjie Wang; Zhongqiang Liu; Xianghuan Luo; Baosong Ma; Yu Chen (Transportation Geotechnics, 2024)

Performance and biotoxicity of electro-Fenton treatment of bisphenol A: Evaluation of copper recovered from microbial fuel cell cathodes for subsequent catalytic applications - Chi-Wen Lin; Guan-Yi Chen; Shu-Hui Liu; Wei Tong Chen; Shih-Hsien Chang; Chih-Yu Ma (Process Safety and Environmental Protection, 2024)

Investigation of factors affecting oil-water separation efficiency in micro-bubble micro-cyclonic flow air flotation - Wei Wang; Xiang Zhao; Xu Bai; Xue-liang Ma; Wei Lin; Jiu-yang Yu (Journal of Water Process Engineering, 2024)

Exploration of the flavor diversity of oolong teas: A comprehensive analysis using metabolomics, quantification techniques, and sensory evaluation - Xiaoxiao Feng; Haoli Wang; Yashu Yu; Yiwen Zhu; Jingke Ma; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Food Research International, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

Janus-Adhesive ionogels for wearable Real-Time monitoring and prevention of infantile meningitis - Xiao-Chun Yang; Xiao-Xue Wang; Chen-Yu Wang; Meng Yin; Ke Ma; Yan Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Study on the optimization of blasting parameters and blastholes charging structure for broken orebody - Kunpeng Yu; Peng Lin; Gideon Chitombo; Liqiang Ma; Chengkun Peng (Tunnelling and Underground Space Technology, 2024)

Decreased nitrogen deposition in Beijing over the recent decade and its implications - Ruotong Si; Ziyin Yu; Xin Ma; Zhang Wen; Ting Luo; Wen Xu; Lei Liu; Aohan Tang; Kai Wang; Lin Zhang; Andreas Schweiger; Keith Goulding; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Arginine and cysteine delay postharvest ripening of tomato fruit by regulating ethylene production - Wenqing Yu; Peihua Ma; Jiping Sheng; Lin Shen (Postharvest Biology and Technology, 2024)

Sustainable double-synergistic silver-hydroxyapatite composite catalyst derived from fish bones for efficient disinfection of Vibrio parahaemolyticus - Di Sun; Tengyang Liao; Hongyong Lin; Yaoyao Sang; Yu Liu; Qingbao Ma; Zhongjie Yu; Bin Zhang; Wei Jiang (Food Chemistry, 2024)

Neutrophil membrane-based biomimetic metal-polyphenol self-assembled nanozyme for the targeting treatment of early brain injury following subarachnoid hemorrhage - Wei Huang; Yu Tian; Jing Ma; Penghui Wei; Chengzhong Du; Xiaodan Zhang; Fuxiang Chen; Yuanxiang Lin; Yang Zhu; Dezhi Kang (Chemical Engineering Journal, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

Weak magnetic field promotes denitrification by stimulating ferromagnetic ion-containing metalloprotein expression - Yuan Lin; Yanting Chen; Haiyue Wang; Yuexin Yu; Yanru Wang; Sijia Ma; Laichun Wang; Hongqiang Ren; Ke Xu (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Saline-alkali land reclamation boosts topsoil carbon storage by preferentially accumulating plant-derived carbon - Lin Chen; Guixiang Zhou; Biao Feng; Chao Wang; Yu Luo; Fang Li; Congcong Shen; Donghao Ma; Congzhi Zhang; Jiabao Zhang (Science Bulletin, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

Identification and health risk assessment of volatile and semi-volatile migrants along with chemical elements in food contact water-borne coating paper - Qing-Hua Yang; Qin-Bao Lin; Xin-Yu Hua; Jia Liao; Shi-Qiang Lu; Ling-Yan Yan; Hong-Sheng Ma (Food Packaging and Shelf Life, 2024)

Spodumene nanosheets@ZrO2-SiO2 heterostructure nanofibers modified separator for long-cycle lithium-sulfur batteries - Lin Li; Bin Yue; Yingying Bao; Shan Jiang; Hong Shao; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2024)

Sleep onset time as a mediator in the association between screen exposure and aging: a cross-sectional study - Senlin Lin; Meng Gao; Juzhao Zhang; Yuting Wu; Tao Yu; Yajun Peng; Yingnan Jia; Haidong Zou; Lina Lu; Deshang Li; Yingyan Ma (GeroScience, 2024)
Excessive screen exposure has become a significant health concern. This study investigates the impact of screen time on aging in middle-aged and elderly populations. Healthy working adults over 45 years old in Shanghai, China, underwent general and ocular examinations. Questionnaires collected demographics, medical history, and screen exposure details. Aging was assessed using the retinal age gap, defined as the difference between the retinal age predicted by deep learning algorithms based on fundus images and chronological age. Pathway analysis tested the mediation effect of sleep duration and onset time on the relationship between screen usage and retinal age gap. The retinal age gap increased with longer screen exposure, from 0.49 ± 3.51 years in the lowest tertile to 5.13 ± 4.96 years in the highest tertile (Jonckheere-Terpstra test, p < 0.001). Each additional hour of screen exposure accelerated the retinal age gap by 0.087 years (95% CI, 0.027, 0.148, p = 0.005) in the fully adjusted linear model. Sleep onset time mediated the impact of screen usage on the retinal age gap (indirect effect, β = 0.11; 95% CI 0.04–0.24). The impact of screen usage in a light-off environment on the retinal age gap was fully mediated by sleep onset time (indirect effect, β = 0.22; 95% CI 0.07–0.38), with the proportion being 100%. Our study identified a correlation between excessive screen time and a wider retinal age gap in middle-aged and elderly individuals, likely due to delayed sleep onset. To mitigate the adverse effects on the retina and aging, it is important to limit screen usage and avoid screens before bedtime.

Tailoring component incorporation for homogenized perovskite solar cells - Wenhan Yang; Junmin Xia; Yuexin Lin; Hao Gu; Fengqiang Ma; Yumin Ren; Fenqi Du; Dejian Yu; Jinfeng Liao; Yiwang Chen; Guojia Fang; Shengchun Yang; et al. (Science Bulletin, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Multifunctional wood-derived cellulose/Ti3C2Tx composite films enhanced by densification strategy for electromagnetic shielding, Joule/solar heating, and thermal camouflage - Qi Liu; Pei-Lin Wang; Wei Zhang; Tian Mai; Meng-Yu Qi; Lei Chen; Junfeng Li; Ming-Guo Ma (Chemical Engineering Journal, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Influence of the natural makeup air system on the kitchen environment in low-energy buildings in severely cold regions - Jiqin Li; Lin Yu; Anqi Liu; Chong Meng; Yingchao Ma; Jiankai Dong (Building and Environment, 2024)

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

Effect of Dietary β-Glucan on Growth Performance, Antioxidant Responses, and Immunological Parameters of Coral Trout (Plectropomus leopardus) - Xiaoqi Hao; Ziyang Lin; Zhenhua Ma; Yukai Yang; Chuanpeng Zhou; Jing Hu; Wei Yu; Heizhao Lin (Fishes, 2024)
Although β-glucan has diverse benefits for fish health, the potential adverse impacts of excessive supplementation are poorly understood. This study investigated the optimal dosage of β-glucan for coral trout and explored the adverse effects of excessive supplementation. The results revealed that moderate β-glucan supplementation (1) significantly enhanced the weight gain rate and specific growth rate (SGR); (2) significantly improved the intestinal villus length (0.10%), muscle thickness (0.05–0.15%), and α-amylase and chymotrypsin activities (0.05–0.15%); (3) significantly increased liver catalase (CAT), glutathione reductase (GR), alkaline phosphatase, complement 3, immunoglobulin M (IgM), lysozyme, serum superoxide dismutase, CAT, glutathione peroxidase, GR, total antioxidant capacity, acid phosphatase, complement 4, and IgM activities and significantly reduced malondialdehyde contents; (4) upregulated genes in the liver associated with copper-zinc superoxide dismutase (SOD-1), manganese superoxide dismutase (SOD-2), CAT, GSH-Px1a, ACP6, AKP, LZ-c, IgM, C3, and C4-b. However, 0.20% β-glucan significantly inhibited the growth performance of coral trout compared with 0.10% β-glucan. Thus, 0.10% β-glucan represents the optimal dosage for promoting growth, antioxidant activity, and immune responses in coral trout, while higher β-glucan levels weakened these beneficial effects. With an SGR established by a cubic regression analysis, the optimal level of β-glucan for maximal growth of coral trout is 0.082%. This study provides new insights into the health impacts of β-glucan on fish.

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Buried interface modification and light outcoupling strategy for efficient blue perovskite light-emitting diodes - Shuxin Wang; Zhiqiu Yu; Jiajun Qin; Guoyi Chen; Yongjie Liu; Shuaiwei Fan; Chao Ma; Fang Yao; Hongsen Cui; Shun Zhou; Kailian Dong; Qianqian Lin; et al. (Science Bulletin, 2024)

Differential expression of ADRB1 causes different responses to norepinephrine in adipocytes of Duroc-Landrace-Yorkshire pigs and min pigs - Yuelei Zhao; Xuexin Li; Wensai Yu; Weimin Lin; Wei Wei; Lifan Zhang; Di Liu; Hong Ma; Jie Chen (Journal of Thermal Biology, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Dynamic role of clean energy and sustainable economic growth in coastal region: Novel observations from China - Qiangqiang Ma; Ruixi Yang; Yu Lin (Environmental Research, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

Biomechanical properties of articular cartilage in different regions and sites of the knee joint: acquisition of osteochondral allografts - Yongsheng Ma; Qitai Lin; Xueding Wang; Yang Liu; Xiangyang Yu; Zhiyuan Ren; Yuanyu Zhang; Li Guo; Xiaogang Wu; Xiangyu Zhang; Pengcui Li; Wangping Duan; et al. (Cell and Tissue Banking, 2024)
Osteochondral allograft (OCA) transplantation involves grafting of natural hyaline cartilage and supporting subchondral bone into the cartilage defect area to restore its biomechanical and tissue structure. However, differences in biomechanical properties and donor-host matching may impair the integration of articular cartilage (AC). This study analyzed the biomechanical properties of the AC in different regions of different sites of the knee joint and provided a novel approach to OCA transplantation. Intact stifle joints from skeletally mature pigs were collected from a local abattoir less than 8 h after slaughter. OCAs were collected from different regions of the joints. The patella and the tibial plateau were divided into medial and lateral regions, while the trochlea and femoral condyle were divided into six regions. The OCAs were analyzed and compared for Young’s modulus, the compressive modulus, and cartilage thickness. Young’s modulus, cartilage thickness, and compressive modulus of OCA were significantly different in different regions of the joints. A negative correlation was observed between Young's modulus and the proportion of the subchondral bone (r = − 0.4241, P < 0.0001). Cartilage thickness was positively correlated with Young’s modulus (r = 0.4473, P < 0.0001) and the compressive modulus (r = 0.3678, P < 0.0001). During OCA transplantation, OCAs should be transplanted in the same regions, or at the closest possible regions to maintain consistency of the biomechanical properties and cartilage thickness of the donor and recipient, to ensure smooth integration with the surrounding tissue. A 7 mm depth achieved a higher Young's modulus, and may represent the ideal length.

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

STON2 variations are involved in synaptic dysfunction and schizophrenia-like behaviors by regulating Syt1 trafficking - Yuanlin Ma; Kai Gao; Xiaoxuan Sun; Jinxin Wang; Yang Yang; Jianying Wu; Anping Chai; Li Yao; Nan Liu; Hao Yu; Yi Su; Tianlan Lu; et al. (Science Bulletin, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Comparison of life cycle assessment between hydrogen production from silicon waste and alkaline water electrolysis - Shengqiang Yang; Dan Mao; Zhiqiang Yu; Wenhui Ma; Lin Ma; Xiufeng Li; Fengshuo Xi (Science of The Total Environment, 2024)

Improving time-series InSAR deformation estimation for city clusters by deep learning-based atmospheric delay correction - Peifeng Ma; Chang Yu; Zeyu Jiao; Yi Zheng; Zherong Wu; Wenfei Mao; Hui Lin (Remote Sensing of Environment, 2024)

An in-situ combo Mo-based ionic liquid and SAPO-11 catalyst for efficient biolipids hydrodeoxygenation and isomerization - Yongxin Ding; Jun Lin; Panjie Yu; Hongwei Zhang; Yongde Ma; Zhenping Cai; Yanning Cao; Kuan Huang; Lilong Jiang (Fuel, 2024)

Theory-guided unraveling of the mechanism underlying Cu1.0/Mn1.0-ZnO with dual reaction centers for enhanced peroxymonosulfate activation - Kaixuan Wang; Haibo Li; Xiaofei Qin; Ting Ma; Lin Zhu; Chenxi Zhang; Wei Yu; Xulun Zhou (Environmental Research, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Towards ecosystem-based management in Chinese coastal areas: Judgement criteria for water-passable structure based on permeability - Lanxiang Liu; Huaming Yu; Xin Qi; Yang Yang; Zixin Lin; Chunxiao Wang; Xiaodong Ma (Ocean & Coastal Management, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

The two-back task leads to activity in the left dorsolateral prefrontal cortex in schizophrenia patients with predominant negative symptoms: a fNIRS study and its implication for tDCS - Chin-Chao Ma; Yen-Yue Lin; Yong-An Chung; Sonya Youngju Park; Cathy Chia-Yu Huang; Wei-Chou Chang; Hsin-An Chang (Experimental Brain Research, 2024)

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Causal effect of air pollution on the risk of cardiovascular and metabolic diseases and potential mediation by gut microbiota - Chen-Xi Liu; Yu-Bo Liu; Yi Peng; Jia Peng; Qi-Lin Ma (Science of The Total Environment, 2024)

Phthalate metabolites in breast milk from mothers in Southern China: Occurrence, temporal trends, daily intake, and risk assessment - Yangyang Liu; Minhua Xiao; Kaiqin Huang; Juntao Cui; Hongli Liu; Yingxin Yu; Shengtao Ma; Xihong Liu; Meiqing Lin (Journal of Hazardous Materials, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

The underappreciated role of fugitive VOCs in ozone formation and health risk assessment emitted from seven typical industries in China - Zhiling Liang; Yunjiang Yu; Bingbing Sun; Qian Yao; Xihua Lin; Yongsheng Wang; Jianping Zhang; Yingzi Li; Xuefeng Wang; Zhengzheng Tang; Shexia Ma (Journal of Environmental Sciences, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Association of household solid fuel use and long-term exposure to ambient air pollution with estimated 10-year high cardiovascular disease risk among postmenopausal women - Ning Chen; Lin-Lin Ma; Yu Zhang; Yu-Xiang Yan (Environmental Pollution, 2024)

Formation mechanism of drift-moat contourite systems revealed by in-situ observations in the South China Sea - Yulong Zhao; Zhifei Liu; Yanwei Zhang; Xiaodong Zhang; Pengfei Ma; Xun Yu; Chen Ling; Baozhi Lin; Jingwen Zhang (Earth and Planetary Science Letters, 2024)

Rapid and efficient preparation of cationized lignin for downstream high value-added utilization of biodegradable antimicrobial nanofibrous membranes - Yu-Fei Gao; Cheng-Ye Ma; Qian Sun; Xin-Xu Zhang; Jing Liu; Jia-Long Wen; Rou-Xi Chen; Hsing-Lin Wang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Overview of life cycle assessment of recycling end-of-life photovoltaic panels: A case study of crystalline silicon photovoltaic panels - Dan Mao; Shengqiang Yang; Lin Ma; Wenhui Ma; Zhiqiang Yu; Fengshuo Xi; Jie Yu (Journal of Cleaner Production, 2024)

Instability in a carbon pool driven by multiple dissolved organic matter sources in a eutrophic lake basin: Potential factors for increased greenhouse gas emissions - Jie Ma; Muchun Zhou; Yu Peng; Ya Tuo; Chuanqiao Zhou; Kexin Liu; Yilin Huang; Fei He; Qiuying Lai; Zhihui Zhang; Tsuyoshi Kinouchi; Shuyin Li; et al. (Journal of Environmental Management, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Neonicotinoids in tea leaves and infusions from China: Implications for human exposure - Qinru Xiao; Xiangyu Li; Shuyang Xu; Xin Chen; Ying Xu; Yu Lu; Langyan Liu; Liyun Lin; Huimin Ma; Shaoyou Lu (Science of The Total Environment, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Enhanced biodegradation kinetics in the copper-polluted sediment through bioaugmentation with water spinach and peanut husk-derived biochar - Lidia Kristia Alfanti; Chih-Yu Ma; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Efficient decontamination of organic pollutants from wastewater by covalent organic framework-based materials - Zixuan Ma; Lin Fang; Lijie Liu; Baowei Hu; Suhua Wang; Shujun Yu; Xiangke Wang (Science of The Total Environment, 2023)

Prediction of cadmium contents in rice grains from Quaternary sediment-distributed farmland using field investigations and machine learning - Xudong Ma; Tao Yu; Dong-Xing Guan; Cheng Li; Bo Li; Xu Liu; Kun Lin; Xuezhen Li; Lei Wang; Zhongfang Yang (Science of The Total Environment, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Evaluation of species thermal sensitivity with individual-based physiological performance - Liang Zhang; Yu-Yang Zhang; Lin-Xuan Ma; Yun-Wei Dong (Marine Environmental Research, 2023)

Extraction of triterpene acids from loquat leaves via a novel hydrophobic deep eutectic solvent screened by COSMO-SAC model - Lu Huang; Yingjie Guo; Tianqi Jin; Ke Yan; Xianglin Liu; Shuyang He; Lin Li; Ye Gong; Junyi Ma; Hang Yu; Zhoumin Lu; Yupeng Liu; et al. (Journal of Cleaner Production, 2023)

Efficient iron single-atom materials for environmental pollutants removal from aqueous solutions: A review - Hairui Hou; Lin Fang; Lijie Liu; Bing Zhao; Dedong Wu; Zixuan Ma; Baowei Hu; Xiangxue Wang; Shujun Yu (Journal of Cleaner Production, 2023)

3D printing of customizable and lightweight multilayer MXene/nanocellulose architectures for tunable electromagnetic interference shielding via direct ink writing - Lei Chen; Tian Mai; Xing-Xiang Ji; Pei-Lin Wang; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Simultaneous enhancement on lignocellulose degradation and humic acid formation using the electric field coupled with an iron anode in the co-composting of food waste and agricultural waste - Yingying He; Rujing Lin; Xuemei Yu; Yike Ma; Jialu Li; Li Xie (Chemical Engineering Journal, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Bacterial metabolism-triggered-chemiluminescence-based point-of-care testing platform for sensitive detection and photothermal inactivation of Staphylococcus aureus - Xinghui Yu; Yongqiang Ma; Siyuan Liu; Chunchun Qi; Weiqi Zhang; Wen Xiang; Zhaoxian Li; Kai Yang; Shaoxian Duan; Xinrao Du; Jian Yu; Yan Xie; et al. (Analytica Chimica Acta, 2023)

Smart enzyme-free amplification dual-mode self-powered platform designed on two-dimensional networked graphdiyne and DNA nanorods for ultra-sensitive detection of breast cancer biomarkers - Yunzhi Ma; Jinyue Shi; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Contrasting laboratory and field outcomes of bat–moth interactions - Aiqing Lin; Jiqian Li; Yinli Hu; Maojun Zhong; Minglun Yu; Nina Ma; Tingting Wei; Jinhong Luo; Jiang Feng (Molecular Ecology, 2023)
Predator–prey interactions are important but difficult to study in the field. Therefore, laboratory studies are often used to examine the outcomes of predator–prey interactions. Previous laboratory studies have shown that moth hearing and ultrasound production can help prey avoid being eaten by bats. We report here that laboratory behavioural outcomes may not accurately reflect the outcomes of field bat–moth interactions. We tested the success rates of two bat species capturing moths with distinct anti‐bat tactics using behavioural experiments. We compared the results with the dietary composition of field bats using next‐generation DNA sequencing. Rhinolophus episcopus and Rhinolophus osgoodi had a lower rate of capture success when hunting for moths that produce anti‐bat clicks than for silent eared moths and earless moths. Unexpectedly, the success rates of the bats capturing silent eared moths and earless moths did not differ significantly from each other. However, the field bats had a higher proportion of silent eared moths than that of earless moths and that of clicking moths in their diets. The difference between the proportions of silent eared moths and earless moths in the bat diets can be explained by the difference between their abundance in bat foraging habitats. These findings suggest that moth defensive tactics, bat countertactics and moth availability collectively shape the diets of insectivorous bats. This study illustrates the importance of using a combination of behavioural experiments and molecular genetic techniques to reveal the complex interactions between predators and prey in nature.

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Environmental exposure to paraben and its association with blood pressure: A cross-sectional study in China - Xu Zhang; Ying Zhang; Hao Lu; Fan Yu; Xueting Shi; Bingchan Ma; Shuang Zhou; Lin Wang; Qing Lu (Chemosphere, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Dioxin emission prediction from a full-scale municipal solid waste incinerator: Deep learning model in time-series input - Chaojun Wen; Xiaoqing Lin; Yuxuan Ying; Yunfeng Ma; Hong Yu; Xiaodong Li; Jianhua Yan (Waste Management, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Inoculation of sulfate-reducing bacteria with a microbial fuel cell to treat groundwater that contains sulfolane: Improving performance, by-products and a biotoxicity assessment - Chi-Wen Lin; Yen-Hua Tseng; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

Cadmium accumulation in paddy soils affected by geological weathering and mining: Spatial distribution patterns, bioaccumulation prediction, and safe land usage - Cheng Li; Zhongfang Yang; Tao Yu; Zhongcheng Jiang; Qibo Huang; Yeyu Yang; Xu Liu; Xudong Ma; Bo Li; Kun Lin; Tengfang Li (Journal of Hazardous Materials, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Biocontrol of Salmonella Typhimurium in milk, lettuce, raw pork meat and ready-to-eat steamed-chicken breast by using a novel bacteriophage with broad host range - Junxin Zhao; Yunzhi Lin; Chen Wang; Mahmoud Zayda; Aye Thida Maung; Tahir Noor Mohammadi; Hoang Minh Duc; Ping Yu; Maomao Ma; Deming Gong; Jun Sato; Yoshimitsu Masuda; et al. (International Journal of Food Microbiology, 2023)

Postharvest fruit quality of tomatoes influenced by an ethylene signaling component during long-term cold storage - Wenqing Yu; Peihua Ma; Jiping Sheng; Lin Shen (Food Chemistry, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Effects of submergence stress on germination and seedling growth of direct-seeded rice and evaluation of submergence tolerance - Rongping Zhang; Ningning Zhou; Lin Zhou; Rigui Ashi; Tingyu Feng; Keyuan Zhang; Xuehuan Liao; Lise Aer; Xia Wu; Kangning Yu; Jianchao Shu; Xuewu He; et al. (Paddy and Water Environment, 2023)

Biogeographic distribution patterns of the bacterial and archaeal communities in two seamounts in the Pacific Ocean - Ning-Hua Liu; Jun Ma; Si-Qi Lin; Kui-Dong Xu; Yu-Zhong Zhang; Qi-Long Qin; Xi-Ying Zhang (Frontiers in Marine Science, 2023)
Seamounts are important components of seafloor topography and have a significant influence on the biogeographic distribution of marine microorganisms. However, current studies on the biogeographic distribution patterns of microorganisms in the ocean around seamounts are still inadequate. This study investigated the bacterial and archaeal communities present in the water column at various depths around the Kocebu and M5 seamounts located in the western Pacific Ocean using 16S rRNA gene high-throughput sequencing. The analyses showed that microbial communities had different alpha diversities and species compositions in samples from the same depth, and disruption of vertical stratification of microbes was observed in deep water layers at both seamounts. The stochastic processes dominated the microbial community assembly around two seamounts, for the Kocebu Seamount, drift accounted for 34.99% and 64.85% in the bacterial and archaeal community assembly processes, respectively; while the corresponding values for the M5 Seamount were 14.07% and 58.65%. Despite the low explanatory power of environmental variables for microbial communities, dissolved inorganic nitrogen was the most significant factor influencing the microbial community structure in seawater around seamounts. Overall, our results revealed that the presence of Kocebu and M5 seamounts enhance the vertical mixing of microbial communities in the surrounding seawater, and stochastic processes dominate microbial community assembly. Considering the numerous seamounts in the global ocean, the impacts of seamounts on marine ecosystems and biogeochemical cycles may have been underestimated.

Dynamic characteristics of heavy metal accumulation in agricultural soils after continuous organic fertilizer application: Field-scale monitoring - Wanchun Sun; Jing Ye; Hui Lin; Qiaogang Yu; Qiang Wang; Zhaoming Chen; Jinchuan Ma; Junwei Ma (Chemosphere, 2023)

Heavy metal contamination collapses trophic interactions in the soil microbial food web via bottom-up regulation - Xuehua Wang; Zhongmin Dai; Jiahui Lin; Haochun Zhao; Haodan Yu; Bin Ma; Lingfei Hu; Jiachun Shi; Xiaoyun Chen; Manqiang Liu; Xin Ke; Yijun Yu; et al. (Soil Biology and Biochemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Increased styrene vapor removal and power production by adding silicone oil to microbial fuel cell-based trickling filter - Wen-Hua Lin; Shu-Hui Liu; Chih-Yu Ma; Chi-Wen Lin (Process Safety and Environmental Protection, 2023)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

A risk-based approach to cumulative effects assessment for large marine ecosystems to support transboundary marine spatial planning: A case study of the yellow sea - Chen Ma; Vanessa Stelzenmüller; Jennifer Rehren; Jing Yu; Zhiwei Zhang; Hao Zheng; Lu Lin; Hee-Cheol Yang; Yinhuan Jin (Journal of Environmental Management, 2023)

Fermentation of grapefruit peel by an efficient cellulose-degrading strain, (Penicillium YZ-1): Modification, structure and functional properties of soluble dietary fiber - Wenjie Ma; Yuting Liang; Huasi Lin; Yi Chen; Jianhua Xie; Fengling Ai; Ziwen Yan; Xiaobo Hu; Qiang Yu (Food Chemistry, 2023)

Distribution of phthalate metabolites, benzophenone-type ultraviolet filters, parabens, triclosan and triclocarban in paired human hair, nail and urine samples - Xiaoyong Tian; Kaiqin Huang; Yangyang Liu; Kaixin Jiang; Ranran Liu; Juntao Cui; Fei Wang; Yingxin Yu; Huanhuan Zhang; Meiqing Lin; Shengtao Ma (Environmental Pollution, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Analysis of influencing factors and prediction of China’s Containerized Freight Index - Xiaoying Tu; Yiling Yang; Yu Lin; Shiqun Ma (Frontiers in Marine Science, 2023)
China, as a major maritime nation, the China Containerized Freight Index (CCFI) serves as an objective reflection of the Chinese shipping market and an important indicator for understanding China’s shipping industry globally. The shipping market is a complex ecosystem influenced by various factors, including vessel supply and demand, cargo supply and demand relationships and prices, fuel prices, and competition from substitute and complementary markets. To analyze and study the state of the Chinese shipping market, we selected the CCFI as an indicator and collected data on six factors that may affect the overall shipping market. These factors include “ the China Coastal Bulk Freight Index(CCBFI)”, “the Baltic Dry Index(BDI)”, “the Yangtze River Container Freight Index”, “Global: Aluminum (minimum purity of 99.5%, London Metal Exchange (LME) spot price): UK landed price”, “Major Ports: Container Throughput”, and “Coal Price: US Central Appalachia: Coal Spot Price Index”. Then, we constructed an analyticaland predictive framework using Deep Neural Network (DNN), CatBoost regression model, and robust regression model to study the CCFI. Based on the R 2 results of the three models, it is evident that DNN provides the best analytical and predictive performance for the CCFI, accurately forecasting its changes. Additionally, the robust regression model indicates that “Global: Aluminum (minimum purity of 99.5%, LME spot price): UK landed price” has the greatest impact on the CCFI. Finally, from a business perspective, we provide some suggestions for China’s container shipping industry.

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Decoupling analysis to assess the impact of land use patterns on carbon emissions: A case study in the Yellow River Delta efficient eco-economic zone, China - Qian Wang; Chuan-hao Yang; Ma-li Wang; Lin Zhao; Yu-chen Zhao; Qi-peng Zhang; Chun-yan Zhang (Journal of Cleaner Production, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Priming effects of nZVI on carbon sequestration and iron uptake are positively mediated by AM fungus in semiarid agricultural soils - Yu-Miao Yang; Minha Naseer; Ying Zhu; Bao-Zhong Wang; Song Wang; Yue Ma; Xiao-Lin Zhang; Xu-Zhe Zhao; Wen-Ying Wang; Shuang-Guo Zhu; Hong-Yan Tao; You-Cai Xiong (Science of The Total Environment, 2023)

Numerical analysis of a modified combined volumetric filtered concentrating PV/T system using MCRT and FVM coupled method - Lin Tu; Yu Ma; Xinyue Han; Mingze Zhu (Journal of Cleaner Production, 2023)

Are the extreme marine heatwave events in the central-eastern tropical Pacific predictable 30–60 days in advance by NUIST CFS1.1 model? - Lin Lin; Yueyue Yu; Chuhan Lu; Jingjia Luo; Lin Chen; Jing Ma; Zhaoyong Guan; Jiye Wu (Atmospheric Research, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Identification of soil parent materials in naturally high background areas based on machine learning - Cheng Li; Chaosheng Zhang; Tao Yu; Xudong Ma; Yeyu Yang; Xu Liu; Qingye Hou; Bo Li; Kun Lin; Zhongfang Yang; Lei Wang (Science of The Total Environment, 2023)

A coupled electrochemical process for schwertmannite recovery from acid mine drainage: Important roles of anodic reactive oxygen species and cathodic alkaline - Ziyuan Huang; Huanxin Ma; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Xiaoyun Yi; Zhi Dang; Chunhua Feng (Journal of Hazardous Materials, 2023)

Off-design characteristics of energy conversion equipment in integrated energy systems - Yu Fu; Haiyang Lin; Biao Feng; Cuiping Ma; Qie Sun; Ronald Wennersten (Journal of Cleaner Production, 2023)

Identification and expression specificity of chemosensory genes in the male reproductive system of Spodoptera exigua - Jing-Hao Hou; Yu He; Yu Ma; Jin-Meng Guo; Zhi-Qiang Wei; Qi Yan; Jin Zhang; Shuang-Lin Dong (Journal of Asia-Pacific Entomology, 2023)

Fatty acid analysis reveals the trophic interactions among organisms in the Zhelin Bay Marine Ranch - Changlin Li; Huijie Lin; Yu Guo; Gang Yu; Zhenhua Ma; Kun Pei; Chuanxin Qin (Frontiers in Marine Science, 2023)
The fatty acid composition in organisms can reflect the trophic level, feeding habits, and utilization of local resources. In the present study, the living resources of different functional areas (artificial reef area, shellfish area, macroalgae area) in the Zhelin Bay Marine Ranch were investigated, and fatty acid analysis was used to elucidate the trophic relations across the food web. The results showed that 22:6ω3 FA (docosahexaenoic acid, DHA), 20:5ω3 FA (eicosapentaenoic acid, EPA), 16:1ω7 FA, and 16:0 FA are fatty acid biomarkers that distinguish carnivorous, omnivorous, and herbivorous organisms. The ratios of DHA/EPA, polyunsaturated fatty acids/saturated fatty acids (PUFA/SFA), and sum of ω3 fatty acids/sum of ω6 fatty acids (Σω3/Σω6) can be used as an important basis to assess the trophic level and feeding habits of organisms. In the comparison of the food web structure of different functional areas, the DHA/EPA ratio of carnivorous organisms in the Artificial Reef area was higher than that in other functional areas due to the abundant living resources, indicating that the food web of the Artificial Reef area presents lower stability to cope with perturbations. Furthermore, MixSIAR was used to quantitatively estimate the diet composition of consumers in the Zhelin Bay Marine Ranch based on their fatty acids. The results of the present study are a valuable contribution to understanding the trophic relationships in the Zhelin Bay Marine Ranch and provide theoretical support for future planning and construction of marine ranches.

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Fabrication of covalent organic frameworks modified nanofibrous membrane for efficiently enriching and detecting the trace polychlorinated biphenyls in water - Yuancai Lv; Jiachen Ma; Zhendong Yu; Shuting Liu; Guifang Yang; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Yongqian Shi; Minghua Liu (Water Research, 2023)

Polybrominated diphenyl ethers and bromophenols in paired serum, hair, and urine samples of e-waste dismantlers: Insights into hair as an indicator of endogenous exposure - Meiqing Lin; Shengtao Ma; Jian Tang; Yingxin Yu; Guiying Li; Ruifang Fan; Guoxia Zhang; Bixian Mai; Taicheng An (Science of The Total Environment, 2023)

Performance of 3D-printed samples based on starch treated by radio frequency energy - Shu Ma; Qianru Zhang; Qian Lin; Lin Pan; Xiuzhu Yu; Hao Jiang (Innovative Food Science & Emerging Technologies, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Structural, mechanical and thermal properties of cubic bixbyite-structured high-entropy oxides - Xinyu Ping; Bin Meng; Xiaohua Yu; Zhiyuan Ma; Xiaoyu Pan; Wu Lin (Chemical Engineering Journal, 2023)

Coating zero valent iron onto hollow carbon spheres as efficient electrocatalyst for N2 fixation and neutral Zn-N2 battery - Huici Qiao; Yu Han; Lin Yao; Xin Xu; Jun Ma; Bin Wen; Jie Hu; Hao Huang (Chemical Engineering Journal, 2023)

Bilayer metal-organic frameworks/MXene/nanocellulose paper with electromagnetic double loss for absorption-dominated electromagnetic interference shielding - Tian Mai; Wen-Yan Guo; Pei-Lin Wang; Lei Chen; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Application of Deep Learning-Based Object Detection Techniques in Fish Aquaculture: A Review - Hanchi Liu; Xin Ma; Yining Yu; Liang Wang; Lin Hao (Journal of Marine Science and Engineering, 2023)
Automated monitoring and analysis of fish’s growth status and behaviors can help scientific aquaculture management and reduce severe losses due to diseases or overfeeding. With developments in machine vision and deep learning (DL) techniques, DL-based object detection techniques have been extensively applied in aquaculture with the advantage of simultaneously classifying and localizing fish of interest in images. This study reviews the relevant research status of DL-based object detection techniques in fish counting, body length measurement, and individual behavior analysis in aquaculture. The research status is summarized from two aspects: image and video analysis. Moreover, the relevant technical details of DL-based object detection techniques applied to aquaculture are also summarized, including the dataset, image preprocessing methods, typical DL-based object detection algorithms, and evaluation metrics. Finally, the challenges and potential trends of DL-based object detection techniques in aquaculture are concluded and discussed. The review shows that generic DL-based object detection architectures have played important roles in aquaculture.

A cross-sectional study of the association between heavy metals and pan-cancers associated with sex hormones in NHANES 1999–2018 - Hai-ming Cao; Ya-zhu Yang; Bao-yi Huang; Yunzhe Zhang; Yu Wu; Zi Wan; Lin Ma (Environmental Science and Pollution Research, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Identification of long non-coding RNA in formaldehyde-induced cardiac dysplasia in rats - Lu Zhang; Yanyan Yang; Lin Zhang; Jianmin Ma; Ruicong Sun; Yu Tian; Xiaoli Yuan; Bingyu Liu; Tao Yu; Zhirong Jiang (Food and Chemical Toxicology, 2023)

Evolvement of carbamazepine under solar irradiation in the presence of chlorine: Efficiency, influences, degradation pathways and ecotoxicity - Haixiang Jia; Xiaoyan Y. Ma; Yu Lin; Shengjiong Yang; Yali An; Yihan Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Simulated impacts of the wetter arid area of Northwestern China on the energy budget and atmospheric circulation over Tibetan Plateau and central part of North China plain in summer - Di Ma; Xianhong Meng; Shihua Lv; Yaohui Li; Haipeng Yu; Lele Shu; Lin Zhao; Zhaoguo Li (Atmospheric Research, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Handwipes as indicators to assess organophosphate flame retardants exposure and thyroid hormone effects in e-waste dismantlers - Jian Tang; Shengtao Ma; Xin Hu; Meiqing Lin; Guiying Li; Yingxin Yu; Taicheng An (Journal of Hazardous Materials, 2023)

Emission, partition, and formation pathway of polychlorinated dibenzo-p-dioxins and dibenzofurans during co-disposal of industrial waste with municipal solid waste - Yuxuan Ying; Yunfeng Ma; Xiaoxiao Wang; Hong Yu; Angjian Wu; Shengyong Lu; Xiaodong Li; Xiaoqing Lin; Lijun Liu; Wenhua Yin (Journal of Environmental Chemical Engineering, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Using a human bronchial epithelial cell-based malignant transformation model to explore the function of hsa-miR-200 family in the progress of PM2.5-induced lung cancer development - Wanli Ma; Lin Xu; Xueying Sun; Yuan Qi; Shen Chen; Daochuan Li; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Jiao Luo; Chuanhai Li; Kunming Zhao; et al. (Environmental Pollution, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Associations between long-term exposure to ambient fine particulate pollution with the decline of kidney function and hyperuricemia: a longitudinal cohort study - Li-Kun Hu; Yu-Hong Liu; Kun Yang; Ning Chen; Lin-Lin Ma; Yu-Xiang Yan (Environmental Science and Pollution Research, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Longitudinal seismic fragility analysis of long tunnels under multiple support excitation - Xiaohong Long; Yongtao Ma; Yu Miao; Lin Ye; Wujun Zhou (Soil Dynamics and Earthquake Engineering, 2023)

Experimental study on the distribution law of the blade foot resistance of a large deep-water open caisson in sand - Bing-nan Jiang; Ting Yu; Wen-ming Peng; Ying-bin Zhang; Shun-bin He; Jian-lin Ma (Ocean Engineering, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Aluminum/lead tetroxide nanothermites for semiconductor bridge applications - Chunpei Yu; Zilong Zheng; Bonan Gu; Yajie Chen; Jianyong Xu; Lin Zhang; Wei Shi; Jiaxin Wang; Changkun Song; Junhong Chen; Kefeng Ma; Wenchao Zhang (Chemical Engineering Journal, 2023)

Effects of dietary chitosan on the growth, health status and disease resistance of golden pompano (Trachinotus ovatus) - Wei Yu; Yukai Yang; Haimin Chen; Qicun Zhou; Yanwa Zhang; Xiaolin Huang; Zhong Huang; Tao Li; Chuanpeng Zhou; Zhenhua Ma; Qiaer Wu; Heizhao Lin (Carbohydrate Polymers, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Novel development of VOx–CeOx–WOx/TiO2 catalyst for low-temperature catalytic oxidation of chloroaromatic organics - Yunfeng Ma; Jianwen Lai; Jiayao Wu; Xiaoqing Lin; Hong Yu; Hao Zhang; Angjian Wu; Jisheng Long; Xiaodong Li (Waste Disposal & Sustainable Energy, 2022)

7-Hydroxy questin, a new anthraquinone from a wetland fungus Aspergillus flavipes PJ03-11 - Chong Yu; Shuang Lin; Xiaorui Ma; Jie Zhang; Caixia Wu; Ben Ma; Haifeng Wang; Yuehu Pei (Natural Product Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

The influence of socioeconomic and environmental determinants on acute myocardial infarction (AMI) mortality from the spatial epidemiological perspective - Yan Wang; Bin Guo; Lin Pei; Hongjun Guo; Dingming Zhang; Xuying Ma; Yan Yu; Haojie Wu (Environmental Science and Pollution Research, 2022)

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Development of wheat-Dasypyrum villosum T6V#4S·6AL translocation lines with enhanced inheritance for powdery mildew resistance - Xiaolan Ma; Yanan Chang; Jingnan Chen; Mei Yu; Baicui Wang; Xingguo Ye; Zhishan Lin (Theoretical and Applied Genetics, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Characterization, risk assessment and resource potential of sediments in the black-odor water in Hunan, China - Jingwei Ma; Xiao Lin; Zefang Yu; Xiang Wang; Jiyi Chen; Qiulai He (Environmental Monitoring and Assessment, 2022)

Effect of bio-based surfactant on wettability of low-rank coal surface and its mechanism - Lin Li; Mingpu Liu; Jianqiao Lyu; Xiaoteng Li; Zhihao Li; Mengyu Lin; Chuandong Ma; Meng He; Qingbiao Wang; Hao Yu; Xiaofang You (Environmental Science and Pollution Research, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Production of sesquiterpene patchoulol in mitochondrion-engineered Saccharomyces cerevisiae - Xin-Yi Tao; Yang-Chen Lin; Feng-Qing Wang; Qing-Hai Liu; Yu-Shu Ma; Min Liu; Dong-Zhi Wei (Biotechnology Letters, 2022)

Frequency design of LEO-based navigation augmentation signals for dual-band ionospheric-free ambiguity resolution - Fujian Ma; Xiaohong Zhang; Jiahuan Hu; Pan Li; Lin Pan; Siqi Yu; Zhiyu Zhang (GPS Solutions, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Kinetics and Size Effects on Adsorption of Cu(II), Cr(III), and Pb(II) Onto Polyethylene, Polypropylene, and Polyethylene Terephthalate Microplastic Particles - Xiaoxin Han; Shiyu Wang; Xue Yu; Rolf D. Vogt; Jianfeng Feng; Lifang Zhai; Weiqi Ma; Lin Zhu; Xueqiang Lu (Frontiers in Marine Science, 2021)
Due to its small size, large specific surface area and hydrophobicity, microplastics, and the adsorbed contaminants may together cause potential negative effects on ecosystems and human beings. In this study, kinetics and size effects on adsorption of Cu(II), Cr(III), and Pb(II) onto PE, PP and PET microplastic particles were explored. Results indicated that the PE and PET microplastics have the higher adsorption capacity for Cu(II), Cr(III), and Pb(II) than that for PP microplastic. The adsorption capacity was affected by microplastic types and metal species. Among the three metals, Pb(II) had the largest adsorption amount on microplastic particles, especially on PET particles. Moreover, the adsorption capacities of microplastics increase with the decrease of particle size. The metal adsorption capacity of <0.9 mm microplastics is greater than that of 0.9–2 mm and 2–5 mm microplastics. The size effect on metal adsorption was largest for PE microplastic. More attention should be paid in case of the coexistence of heavy metals and tiny PE and PET microplastics in the environment.

Expression profiling of WRKY transcription factors in Spinach - Yaying Ma; Shuai Chen; Hongying Yu; Ruoyu Li; Zhicong Lin; Mingxing Cai; Min Tang; Xingtan Zhang; Ray Ming (Euphytica, 2021)

Harmful algal bloom-forming dinoflagellate Prorocentrum donghaiense inhibits the growth and photosynthesis of seaweed Sargassum fusiformis embryos - Caixia Wang; Min Wang; Binbin Chen; Wenli Qin; Lidong Lin; Chuanjun Dai; Hengguo Yu; Renhui Li; Min Zhao; Zengling Ma (Journal of Oceanology and Limnology, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Capacity of transportation and spread of COVID-19—an ironical fact for developed countries - Li Ma; Zhuo Yu; Yan Jiao; Lin Lin; Wei Zhong; Sara W. Day; Arnold Postlethwaite; Hong Chen; Qiang Li; Heliang Yin; Gang Wang (Environmental Science and Pollution Research, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Houcaris gen. nov. from the early Cambrian (Stage 3) Chengjiang Lagerstätte expanded the palaeogeographical distribution of tamisiocaridids (Panarthropoda: Radiodonta) - Yu Wu; Dongjing Fu; Jiaxin Ma; Weiliang Lin; Ao Sun; Xingliang Zhang (PalZ, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Influences of organic material application on the physically separated soil organic carbon and nitrogen fractions in rice fields - Qiaogang Yu; Jing Ye; Wanchun Sun; Hui Lin; Qiang Wang; Junwei Ma (Journal of Soils and Sediments, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Transcriptional analysis reveals physiological response to acute acidification stress of barramundi Lates calcarifer (Bloch) in coastal areas - Zhenhua Ma; Xing Zheng; Zhengyi Fu; Siqi Lin; Gang Yu; Jian G. Qin (Fish Physiology and Biochemistry, 2020)

Eddy-resolving Simulation of CAS-LICOM3 for Phase 2 of the Ocean Model Intercomparison Project - Yiwen Li; Hailong Liu; Mengrong Ding; Pengfei Lin; Zipeng Yu; Yongqiang Yu; Yao Meng; Yunlong Li; Xiaodong Jian; Jinrong Jiang; Kangjun Chen; Qian Yang; et al. (Advances in Atmospheric Sciences, 2020)
A 61-year (1958–2018) global eddy-resolving dataset for phase 2 of the Ocean Model Intercomparison Project has been produced by the version 3 of Chinese Academy of Science, the State Key Laboratory of Numerical Modeling for Atmospheric Sciences and Geophysical Fluid Dynamics/Institute of Atmospheric Physics (LASG/IAP) Climate system Ocean Model (CAS-LICOM3). The monthly and a part of the surface daily data in this study can be accessed on the Earth System Grid Federation (ESGF) node. Besides the details of the model and experiments, the evolutions and spatial patterns of large-scale and mesoscale features are also presented. The mesoscale features are reproduced well in the high-resolution simulation, as the mesoscale activities can contribute up to 50% of the total SST variability in eddy-rich regions. Also, the large-scale circulations are remarkably improved compared with the low-resolution simulation, such as the climatological annual mean SST (the RMSE is reduced from 0.59°C to 0.47°C, globally) and the evolution of Atlantic Meridional Overturning Circulation. The preliminary evaluation also indicates that there are systematic biases in the salinity, the separation location of the western boundary currents, and the magnitude of eddy kinetic energy. All these biases are worthy of further investigation.

FGOALS-g3 Model Datasets for CMIP6 Flux-Anomaly-Forced Model Intercomparison Project - Yaqi Wang; Zipeng Yu; Pengfei Lin; Hailong Liu; Jiangbo Jin; Lijuan Li; Yanli Tang; Li Dong; Kangjun Chen; Yiwen Li; Qian Yang; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) is an endorsed Model Intercomparison Project in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The goal of FAFMIP is to investigate the spread in the atmosphere-ocean general circulation model projections of ocean climate change forced by increased CO 2 , including the uncertainties in the simulations of ocean heat uptake, global mean sea level rise due to ocean thermal expansion and dynamic sea level change due to ocean circulation and density changes. The FAFMIP experiments have already been conducted with the Flexible Global Ocean-Atmosphere-Land System Model, gridpoint version 3.0 (FGOALS-g3). The model datasets have been submitted to the Earth System Grid Federation (ESGF) node. Here, the details of the experiments, the output variables and some baseline results are presented. Compared with the preliminary results of other models, the evolutions of global mean variables can be reproduced well by FGOALS-g3. The simulations of spatial patterns are also consistent with those of other models in most regions except the North Atlantic and the Southern Ocean, indicating large uncertainties in the regional sea level projections of these two regions.

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

Quantitative Relationship Between Argillaceous Caprock Thickness and Maximum Sealed Hydrocarbon Column Height - Cunfei Ma; Chengyan Lin; Chunmei Dong; Guoqiang Luan; Yu Zhang; Xiaolong Sun; Xiaocen Liu (Natural Resources Research, 2020)

Erratum to: LICOM Model Datasets for the CMIP6 Ocean Model Intercomparison Project - Pengfei Lin; Zipeng Yu; Hailong Liu; Yongqiang Yu; Yiwen Li; Jinrong Jiang; Wei Xue; Kangjun Chen; Qian Yang; Bowen Zhao; Jilin Wei; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

The effects of maternal exposure to BPA during pregnancy on the male reproductive system and the testicular microRNA expression profile - Lin Ma; Haiyang Yu; Xu Wang; Dan Li; Yumin Zhang; Xiucong Pei; Zhiwen Duan; Mingyue Ma (Environmental Science and Pollution Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

LICOM Model Datasets for the CMIP6 Ocean Model Intercomparison Project - Pengfei Lin; Zhipeng Yu; Hailong Liu; Yongqiang Yu; Yiwen Li; Jirong Jiang; Wei Xue; Kangjun Chen; Qian Yang; Bowen Zhao; Jilin Wei; Mengrong Ding; et al. (Advances in Atmospheric Sciences, 2020)
The datasets of two Ocean Model Intercomparison Project (OMIP) simulation experiments from the LASG/IAP Climate Ocean Model, version 3 (LICOM3), forced by two different sets of atmospheric surface data, are described in this paper. The experiment forced by CORE-II (Co-ordinated Ocean–Ice Reference Experiments, Phase II) data (1948–2009) is called OMIP1, and that forced by JRA55-do (surface dataset for driving ocean–sea-ice models based on Japanese 55-year atmospheric reanalysis) data (1958–2018) is called OMIP2. First, the improvement of LICOM from CMIP5 to CMIP6 and the configurations of the two experiments are described. Second, the basic performances of the two experiments are validated using the climatological-mean and interannual time scales from observation. We find that the mean states, interannual variabilities, and long-term linear trends can be reproduced well by the two experiments. The differences between the two datasets are also discussed. Finally, the usage of these data is described. These datasets are helpful toward understanding the origin system bias of the fully coupled model.

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

In situ tests on improvement of collapsible loess with large thickness by down-hole dynamic compaction pile - Yu-chuan Zhang; Yong-guo Yao; An-gang Ma; Chen-lin Liu (European Journal of Environmental and Civil Engineering, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

C, N, and P stoichiometry and their interaction with different plant communities and soils in subtropical riparian wetlands - Meng-Fei Yu; Yongxia Tao; Wenzhi Liu; Wei Xing; Guihua Liu; Lai Wang; Lin Ma (Environmental Science and Pollution Research, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

LLCLPLDA: a novel model for predicting lncRNA–disease associations - Guobo Xie; Shuhuang Huang; Yu Luo; Lei Ma; Zhiyi Lin; Yuping Sun (Molecular Genetics and Genomics, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

Contributions of biotic and abiotic processes to the presence of an aggregate hierarchy in three different mineral soils in an experimental incubation study - Zhenghong Yu; Lin Chen; Jiabao Zhang; Yanyun Zheng; Congzhi Zhang; Donghao Ma; Guixiang Zhou (Journal of Soils and Sediments, 2019)

Quantitative trait locus mapping for panicle exsertion length in common wheat using two related recombinant inbred line populations - Yang Tao; Xin Yi; Yu Lin; Zhiqiang Wang; Fangkun Wu; Xiaojun Jiang; Shihang Liu; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; Youliang Zheng; et al. (Euphytica, 2019)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Assessing the efficacy of a live vaccine against avian encephalomyelitis virus - Wencheng Lin; Piaopiao Lu; Aijun Li; Yu Wu; Hongxin Li; Feng Chen; Jingyun Ma; Qingmei Xie (Archives of Virology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Characterization of the complete mitochondrial genome sequence of the Asiatic toad Bufo gargarizans (Amphibia, Anura, Bufonidae) with phylogenetic analysis - Lichun Jiang; Min Zhang; Jie Liu; Lin Ma; Peng Yu; Qiping Ruan (Conservation Genetics Resources, 2018)

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)

A study on the role that quorum sensing play in antibiotic-resistant plasmid conjugative transfer in Escherichia coli - Yueheng Zhang; Qingping Ma; Bingmei Su; Rui Chen; Juan Lin; Zhifen Lin; Dali Wang; Yang Yu (Ecotoxicology, 2018)

Integrative Application of Life Cycle Assessment and Risk Assessment to Environmental Impacts of Anthropogenic Pollutants at a Watershed Scale - Xiaodan Lin; Shen Yu; Hwongwen Ma (Bulletin of Environmental Contamination and Toxicology, 2018)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

Influences of Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on Heavy Metals and Inorganic Nitrogen Transformation in the Rice Field Surface Water - Qiaogang Yu; Junwei Ma; Wanchun Sun; Hui Lin; Qiang Wang; Jianrong Fu (Water, Air, & Soil Pollution, 2017)

In vitro and in vivo studies of nematophagous fungi Arthrobotrys musiformis and Arthrobotrys robusta against the larvae of the trichostrongylides - Kui Zheng Cai; Bo Bo Wang; Qiang Xu; Jun Lin Liu; Kang Ying Wang; Yu Jia Xue; Hai Yan Zhang; Hai Yu Wang; Xin Cao; Zhong Ren Ma (Acta Parasitologica, 2017)
Six isolates of

Aneuploid progenies of triploid hybrids between diploid and tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Zhong-Qiao Lin; Tian-Yu Ma; Yi Sui; Katsutoshi Arai (Genetica, 2016)

FGF21 ameliorates nonalcoholic fatty liver disease by inducing autophagy - Shenglong Zhu; Yunzhou Wu; Xianlong Ye; Lei Ma; Jianying Qi; Dan Yu; Yuquan Wei; Guangxiao Lin; Guiping Ren; Deshan Li (Molecular and Cellular Biochemistry, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Investigation of peat sediments from Daiyun Mountain in southeast China: late Holocene vegetation, climate and human impact - Lin Zhao; Chunmei Ma; Lingyu Tang; Kam-biu Liu; Limi Mao; Yu Zhang; Huayu Lu; Shuangye Wu; Qingyun Tu (Vegetation History and Archaeobotany, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Therapy with the Combination of Amlodipine and Irbesartan Has Persistent Preventative Effects on Stroke Onset Associated with BDNF Preservation on Cerebral Vessels in Hypertensive Rats - Yu Hasegawa; Takashi Nakagawa; Ken Uekawa; Mingjie Ma; Bowen Lin; Hiroaki Kusaka; Tetsuji Katayama; Daisuke Sueta; Kensuke Toyama; Nobutaka Koibuchi; Shokei Kim-Mitsuyama (Translational Stroke Research, 2016)

Radioactive source terms for the Fukushima nuclear accident - WuHui Lin; LiQi Chen; Wen Yu; Hao Ma; Zhi Zeng; Shi Zeng (Science China Earth Sciences, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Lineage distribution and E2 sequence variation of high-risk human papillomavirus types isolated from patients with cervical cancer in Sichuan province, China - Haijing Wu; Enqi Wu; Lin Ma; Guonan Zhang; Yu Shi; Jianming Huang; Xiao Zha (Archives of Virology, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Phylogenetic diversity on housekeeping and symbiotic genes of rhizobial from Sphaerophysa in China - Lin Xu; Osama Abdalla Mohamad; Yin Shan Ma; Yu Mei Zhang; Zhao Yu Kong (World Journal of Microbiology and Biotechnology, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Relationship between cell-indicated earth pressures and field earth pressures in backfills - Ji-cheng Wang; Jian-lin Yu; Shi-guo Ma; Xiao-nan Gong (European Journal of Environmental and Civil Engineering, 2015)

Research on Chinese public finance in response to domestic natural disasters - Yong-ling Zhang; Yan-nan Ma; An Chen; Yu-han Lin (Natural Hazards, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Geotechnical hazards assessment on wind-eroded desert embankment in Inner Mongolia Autonomous Region, North China - Chi Li; Hao Huang; Lin Li; Yu Gao; Yunfeng Ma; Farshad Amini (Natural Hazards, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

QTLs for uppermost internode and spike length in two wheat RIL populations and their affect upon plant height at an individual QTL level - Ma Yu; Shuang-Lin Mao; Guo-Yue Chen; Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Euphytica, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

GSK3β Promotes the Differentiation of Oligodendrocyte Precursor Cells via β-Catenin-Mediated Transcriptional Regulation - Liang Zhou; Chong-Yu Shao; Si-min Xu; Jiao Ma; Ya-Jun Xie; Lin Zhou; Peng Teng; Yin Wang; Mengsheng Qiu; Ying Shen (Molecular Neurobiology, 2014)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

Formation, regeneration, and transformation of protoplasts of Streptomyces diastatochromogenes 1628 - Zheng Ma; Jinxiu Liu; Xiaozhen Lin; Xuping Shentu; Yalin Bian; Xiaoping Yu (Folia Microbiologica, 2014)

CarNAC2, a novel NAC transcription factor in chickpea (Cicer arietinum L.), is associated with drought-response and various developmental processes in transgenic arabidopsis - Xingwang Yu; Hui Peng; Yanmin Liu; Yan Zhang; Yingjie Shu; Quanjia Chen; Shubing Shi; Lin Ma; Hao Ma; Hua Zhang (Journal of Plant Biology, 2014)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Relationship Between Myocardial Bridging and Coronary Arteriosclerosis - Jian Ling Sun; Wei Min Huang; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Transcriptional responses to drought stress in root and leaf of chickpea seedling - Xiansheng Wang; Ying Liu; Yuying Jia; Hanyan Gu; Hongyu Ma; Tian Yu; Hua Zhang; Quanjia Chen; Lin Ma; Aixing Gu; Jusong Zhang; Shubing Shi; et al. (Molecular Biology Reports, 2012)

Isolation and characterization of a long-chain acyl-coenzyme A synthetase encoding gene from the marine microalga Nannochloropsis oculata - Lin Zhang; Xiaolei Ma; Guanpin Yang; Baohua Zhu; Jichang Han; Wengong Yu; Kehou Pan (Journal of Applied Phycology, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Role of Lys281 in the Dunaliella salina (6-4) Photolyase Reaction - Feiwei Zhang; Hui Xu; Yu Cao; Tao Wen; Jiafu Lin; Gen Ma; Dairong Qiao; Yi Cao (Current Microbiology, 2011)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Artificial gynogenesis and assessment of homozygosity in meiotic gynogens of spotted halibut (Verasper variegatus) - Xiang-Shan Ji; Song-Lin Chen; Jing-Feng Yang; Hong-Yu Ma; Yun-Liang Jiang (Aquaculture International, 2010)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

In-Silico Approaches to Multi-target Drug Discovery - Xiao Hua Ma; Zhe Shi; Chunyan Tan; Yuyang Jiang; Mei Lin Go; Boon Chuan Low; Yu Zong Chen (Pharmaceutical Research, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Construction of a Genetic Linkage Map and Mapping of a Female-Specific DNA Marker in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Xiaolin Liao; Hong-Yu Ma; Gen-Bo Xu; Chang-Wei Shao; Yong-Sheng Tian; Xiang-Shan Ji; Jing-Feng Yang; Song-Lin Chen (Marine Biotechnology, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Effects of dietary medicinal herbs and Bacillus on survival, growth, body composition, and digestive enzyme activity of the white shrimp Litopenaeus vannamei - Ming-Chao Yu; Zhuo-Jia Li; Hei-Zhao Lin; Guo-Liang Wen; Shen Ma (Aquaculture International, 2009)

Development of polymorphic microsatellite markers from barfin flounder (Verasper moseri) and their cross-species amplification - Gui-Dong Miao; Chang-Wei Shao; Xiao-Lin Liao; Hong-Yu Ma; Yong-Sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

Effects of Silver on the Photocatalytic Degradation of Gaseous Isopropanol - Chih-Ming Ma; Young Ku; Yu-Lin Kuo; Yiang-Chen Chou; Fu-Tien Jeng (Water, Air, & Soil Pollution, 2009)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China - Yinghui Li; Rongxia Guan; Zhangxiong Liu; Yansong Ma; Lixia Wang; Linhai Li; Fanyun Lin; Weijiang Luan; Pengyin Chen; Zhe Yan; Yuan Guan; Li Zhu; et al. (Theoretical and Applied Genetics, 2008)

Effects of dietary Bacillus and medicinal herbs on the growth, digestive enzyme activity, and serum biochemical parameters of the shrimp Litopenaeus vannamei - Ming-Chao Yu; Zhuo-Jia Li; Hei-Zhao Lin; Guo-Liang Wen; Shen Ma (Aquaculture International, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)